Pain phenotypes among adults living with cerebral palsy and spina bifida. Issue 10 (October 2021) - Peterson, Mark D.; Haapala, Heidi; Kamdar, Neil; Lin, Paul; Hurvitz, Edward A.
Abstract : Abstract: Chronic pain is the most commonly reported physical symptomology of cerebral palsy (CP) and spina bifida (SB) throughout the lifespan, and yet, pain is perhaps the least understood comorbidity in these populations. The objective of this study was to compare the prevalence and types of pain diagnosed among adults living with and without CP or SB. In this retrospective cohort study, we analyzed data from a nationwide commercial insurance claims database. Beneficiaries were included if they had an International Classification of Diseases, Ninth revision, Clinical Modification diagnosis code for CP or SB (n = 22, 648). Adults without CP or SB were also included as controls (n = 931, 623). Pain phenotypes (nociceptive, nociplastic, and neuropathic pain) and pain multimorbidity (≥2 conditions) were compared. We found that adults living with CP or SB had a higher prevalence of any pain disorders (55.9% vs 35.2%), nociceptive pain (44.0% vs 26.7%), nociplastic pain (26.1% vs 11.9%), neuropathic pain (9.6% vs 5.6%), and pain multimorbidity (21.1% vs 8.4%), as compared to adults without CP or SB, and differences were to a clinically meaningful extent. Adjusted odds ratios of nociceptive pain (odds ratio [OR]: 2.20; 95% confidence interval [CI]: 2.15-2.24), nociplastic pain (OR: 2.47; 95% CI: 2.41-2.53), neuropathic pain (OR: 2.71; 95% CI: 2.54-2.89), and other pain (OR: 3.92; 95% CI: 3.67-4.19) were significantly higher for adults living with CP or SB. In conclusion, adults with CP or SB have a significantly higher prevalence and odds of common peripheral, central, and neuropathic pain disorders and pain multimorbidity, as compared to adults without CP or SB. Abstract : Supplemental Digital Content is Available in the Text.Adults with cerebral palsy or spina bifida have an elevated risk of a variety of pain subtypes (including nociplastic, neuropathic, and nociceptive pain) and pain multimorbidity, as compared to the general adult population without cerebral palsy or spina bifida.